SDN implementation in NTT communications - Xianwei XU; Jinyuan ZHU; Fengmao DU; Jianwei CAO (Dianxin kexue)
The practical instances of SDN/NFV technologies applied in communications were discussed,and the exploration and the latest development of NTT in this field were primarily analyzed.After the comparison of the developing strategies of foreign market and domestic market,the constructive suggestion of deploying SDN/NFV technologies effectively in Chinese market was concluded.